Hubungan Self Efficacy dengan Perilaku Bullying di SD Negeri 06 Sungai Kayu Ara Kecamatan Sungai Apit Kabupaten Siak - Tia Salsabilla; Deprizon Deprizon; Salman Salman (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
There are many cases of bullying at school so it can have a bad impact, bullying among students is a serious problem that has a negative impact on the victim and the school environment as a whole and bullying can also reduce the level of self-confidence of students who experience bullying. The aim of this research is to determine the relationship between self-efficacy and bullying behavior. The research method used in this research is descriptive quantitative. Data was obtained through questionnaires distributed in schools. The research results show that self-efficacy has a significant relationship with bullying behavior.